A multidirectional conditional spectrum. (7th December 2017) - Nievas, Cecilia; Sullivan, Timothy
Summary: This paper presents a procedure to generate multidirectional conditional spectra (MDCS) that allow for the characterisation of seismic demands at different angles of incidence. Being conditional on a particular period and its direction of maximum response, it is considered to be a natural evolution of the conditional spectrum to account for the effects of directionality, that is, the variation of seismic demands as a function of the angle of incidence of ground motions, which can have a significant effect on the performance of different kinds of structures. The three main components needed for the generation of MDCS are explained in detail. Monte Carlo simulations are conducted using different sampling methods to assess the effects of incorporating the correlation between demands at different orientations for the same oscillator period, and a novel correlation model is proposed for this purpose. The statistical characteristics of MDCS, their relation with the conditional spectrum, the advantages of the MDCS over previous definitions of orientation‐specific spectra, and prospective future developments are discussed.